Macroeconomic Responses to Terms-of-Trade Shocks : A Framework for Policy Analysis for the Argentine Economy - Berkmen, Pelin (IMF Working Papers; Working Paper ;, 2009)
This paper presents a version of the global integrated monetary fiscal (GIMF) model adapted and calibrated to the Argentine economy. The model replicates the effect of the strong improvement in Argentina's terms of trade stemming from higher world commodity prices as well as other key economic trends in Argentina during the period 2003-2007. The model can be used to assess the potential impact of different combinations of monetary and fiscal policies on output, inflation, and the external trade.